The Invisible Whiteness of Being: Gary Filmon and the Mainstream Media - Carlyle, Elizabeth (Ethnologies, 1997)
This paper revolves around local and experiential facets of the ways in which whiteness is mobilized by both politicians and the mainstream media. Its focus is Manitoba Premier Gary Filmon who, the author argues, simultaneously employs the paradoxical and vacuous meanings of whiteness. The author traces some of the history of current discourse on concepts of whiteness (and the corollary, blackness or non-whiteness), with the aim of elucidating how Filmons success relies on manufacturing an image of himself that revolves around the potent invisibility of whiteness. Approaching the discussion through interpretations of mainstream media representations, the author argues that Filmon mobilizes a strategic image of whiteness that is related to denying the special interests of whiteness and that appeals to humanistic and capitalist sentiments of equality for all, while at the same time constructing whiteness as a universal ideal.